Donor pretreatment with nebulized complement C3a receptor antagonist mitigates brain‐death induced immunological injury post–lung transplant. Issue 10 (10th April 2018) - Cheng, Qi; Patel, Kunal; Lei, Biao; Rucker, Lindsay; Allen, D. Patterson; Zhu, Peng; Vasu, Chentha; Martins, Paulo N.; Goddard, Martin; Nadig, Satish N.; Atkinson, Carl
Abstract : Donor brain death (BD) is an inherent part of lung transplantation (LTx) and a key contributor to ischemia‐reperfusion injury (IRI). Complement activation occurs as a consequence of BD in other solid organ Tx and exacerbates IRI, but the role of complement in LTx has not been investigated. Here, we investigate the utility of delivering nebulized C3a receptor antagonist (C3aRA) pretransplant to BD donor lungs in order to reduce post‐LTx IRI. BD was induced in Balb/c donors, and lungs nebulized with C3aRA or vehicle 30 minutes prior to lung procurement. Lungs were then cold stored for 18 hours before transplantation into C57Bl/6 recipients. Donor lungs from living donors (LD) were removed and similarly stored. At 6 hours and 5 days post‐LTx, recipients of BD donor lungs had exacerbated IRI and acute rejection (AR), respectively, compared to recipients receiving LD lungs, as determined by increased histopathological injury, immune cells, and cytokine levels. A single pretransplant nebulized dose of C3aRA to the donor significantly reduced IRI as compared to vehicle‐treated BD donors, and returned IRI and AR grades to that seen following LD LTx. These data demonstrate a role for complement inhibition in the amelioration of IRI post‐LTx in the context of donor BD. Abstract : In a murine model, nebulized treatment of the brain dead donor lung with a complement C3a receptor antagonist significantly reduces ischemia‐reperfusion injury, and further reduces the tempo of acute rejection.